UAV-IRS Assisted Full-Duplex Covert Communication: Joint Optimization of Phase Shift and 3D Trajectory - Pengwu Wan; Xiaolin Dong; Dongrui Chen; Xi Hui; Jin Wang (IEEE Access, 2025)
This paper proposes a novel strategy to enhance covert communication performance through a full-duplex communication system assisted by Unmanned Aerial Vehicles (UAV) and Intelligent Reflecting Surfaces (IRS). In the proposed system, the base station (Alice) leverages the IRS mounted on UAV to reflect covert information towards the legitimate full-duplex receiver (David). As a full-duplex receiver, David actively generates dynamic artificial noise (AN) to deceive the warden (Eve) and obscure her detection capability. Notably, due to the adversarial nature of the scenario, Eve’s exact location remains unknown to the legitimate parties. Within this framework, we first derive the minimum detection error probability (DEP) for Eve under the worst-case scenario, where Eve employs the optimal detection threshold. Subsequently, we formulate an optimization problem aimed at maximizing the covert transmission rate while satisfying the covertness constraint by alternately optimizing the IRS phase shifts and the three-dimensional (3D) trajectory of UAV. Simulation results validate the effectiveness of the proposed strategy in enhancing covert communication performance, particularly in non-line-of-sight (NLOS) environments.